Odpowiedzi

2009-11-19T23:07:02+01:00
5pierw.2 + 3 podzielone przez5 pierw.2 -3 =
=(5√2+3)(5√2+3):[(5√2-3)(5√2+3)]=
=[50+30√2+9]:(50-9)=(59+30√2):41
2009-11-19T23:07:34+01:00
(5√2 +3) / (5√2 -3) // * (5√2 +3) / (5√2 +3) =
(5√2 +3)² / (25 *2 -9) =
(50 +30√2 + 9) / 41 =
(59 +30√2) / 41 = // √2 ≈ 1,4142
(59 + 42,4264) / 41 = 2,4738

Pozdrawiam ;)
Najlepsza Odpowiedź!
2009-11-20T01:14:20+01:00
5√2+ 3 /5 √2 -3=(5√2+ 3 )(5 √2 +3)/(5 √2 -3)((5 √2 +3)=
(50+ +30 √2 +9)/(50 -9)=(59+ +30 √2 )/(41)=59/41+30√2/41